The generation game. (Economist, 2023)
The article focuses on the existential threat posed by generative artificial intelligence (AI) and large language model (LLM). Topics discussed include contemporary explosion of the capabilities of AI software, neural networks embedded in software with broader functionality and abilities across a variety of different LLMs.